A Survey on Challenges and Techniques of Sentiment Analysis - Shiramshetty Gouthami, Dr. Nagaratna P Hegde (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The billions of users share and exchange their opinions on web through different social platforms like twitter, Facebook, Amazon and other product review sites about different problems like products, events, persons or any organizations with the vast developing technology today.Thus the sentiments have been generated by the large number of users on different types of entities which are more useful for the organizations, businesses and even individual also. The sentiment analysis is thus required for this to extract Abstract:The useful information from the large number of resources by using the text analysis and natural language processing techniques. Sentiment analysis is the most significant aspect for the various business and government organization in order to achieve high and better accurate prediction on their future actions based on the opinions from users but the process of this sentiment analysis has been facing different challenges. These challenges become difficulty in analyzing the accurate meaning of sentiments and detecting the suitable sentiment polarity. In this paper a survey on challenges and techniques of sentiment analysis is presented. Various approaches and methodology used in Sentiment Analysis and challenges relevant to their approaches and techniques are covered in this paper. The focus is on Internet text like, Product review, tweets and other social media.